2022
DOI: 10.1136/bcr-2022-249819
|View full text |Cite
|
Sign up to set email alerts
|

Pyridostigmine-induced coronary artery spasm in early-onset myasthenia gravis: a case presentation and review of the literature

Abstract: We present a case of pyridostigmine-induced coronary artery spasm in a woman with early-onset myasthenia gravis (MG) who suffered from acute chest discomfort a few days after pyridostigmine dose up-titration. Twelve-lead ECG demonstrated ST-segment elevation in inferior limb leads together with sinus arrest. Sublingual nitrate was immediately given, which rapidly relieved her symptoms concomitantly with the resolution of abnormal ECG findings. Coronary angiography showed normal coronary arteries reflecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Intracoronary isosorbide dinitrate and adenosine relieved the symptoms. Chuapakdee et al [ 18 ] also reported a case of CSA after pyridostigmine dose up-titration. Sublingual nitrate immediately relieved symptoms concomitantly with the resolution of abnormal electrocardiograph findings.…”
Section: Introductionmentioning
confidence: 99%
“…Intracoronary isosorbide dinitrate and adenosine relieved the symptoms. Chuapakdee et al [ 18 ] also reported a case of CSA after pyridostigmine dose up-titration. Sublingual nitrate immediately relieved symptoms concomitantly with the resolution of abnormal electrocardiograph findings.…”
Section: Introductionmentioning
confidence: 99%